Financial Literacy, Retirement Planning, and Demand for Life Insurance: Evidence from Lagos State-owned Tertiary Institutions - Sunday Stephen Ajemunigbohun; Rasheed Olawale Azeez (Journal of International Business, Economics and Entrepreneurship)
Financial literacy is a protective tool for ensuring quality retirement life through annuity life insurance policy. The study assessed how financial literacy measures and retirement planning impact the demand for life insurance among university instructors at tertiary institutions owned by Lagos State. The research study used a cross-sectional survey research design, incorporating multiphase sampling approaches. Completed structured questionnaire from two hundred and seventy-three respondents were gathered from university lecturers in Lagos State-Owned tertiary institutions, and data were analysed using simple frequency percentages and multiple regression technique. Although there is a positive correlation between financial attitude, financial knowledge, and financial behaviour with the demand for life insurance, the variable of financial confidence shows an inverse correlation. The demand for life insurance is positively and significantly influenced by retirement planning. Therefore, it is recommended that ongoing endeavours be made to educate the general population on the significance of life insurance for improved financial planning. This, in turn, helps insurers to understand and serve suitable insurance plan that fits their clients’ financial plan.